Building a better measure of school quality. (April 2017) - Schneider, Jack; Jacobsen, Rebecca; White, Rachel; Gehlbach, Hunter
When it comes to measuring the quality of a school, policy leaders tend to embrace standardized tests as the go-to indicator, whereas parents and community members tend to rely on reputation, word-of-mouth, and what they perceive with their own eyes. The authors suggest a better approach: a new framework that looks at three categories of inputs (the teaching environment, school culture, and resources) as well as two categories of outputs (academic learning and cultivation of student character and well-being). Parents and community members who used the new interactive tool came away with significantly more positive perceptions of unfamiliar schools .